Peran Bahasa Indonesia sebagai Alat Inklusi dan Harmonisasi di Lingkungan Perkantoran Multikultural - Mareta, Syifa Aulia; Fauziah, Aisyah Syifa; Alyan, Yudha Muhammad; Aldiarti, Yuni; Fitriyani, Aisyah; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the importance of the role of Indonesian as a tool for inclusion and harmonization in a multicultural office environment. The method used in the study is a qualitative approach with a descriptive method used to explain in detail and in detail how important the role of Indonesian is in uniting cultural differences, namely as a language of unity. Data collection was carried out through interviews conducted with several employees working in companies with diverse scopes. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. Based on the results of data analysis, it was found that the main problems related to communication between employees in a multicultural office environment. Indonesian plays a key role in effectively resolving these challenges. The results of the study show that Indonesian has a significant role as a tool that helps facilitate cross-cultural understanding and cooperation in the workplace. By using Indonesian as the main medium of communication, employees from different cultural backgrounds can interact more effectively and harmoniously. Thus, the conclusion of this study emphasizes the importance of the role of the Indonesian language in creating inclusion and harmonization in the multicultural office environment